2020
DOI: 10.2174/1389200221999200901202945
|View full text |Cite
|
Sign up to set email alerts
|

In Silico ADMET Evaluation of Natural DPP-IV Inhibitors for Rational Drug Design against Diabetes

Abstract: Background: As a metabolic and lifestyle disorder, diabetes mellitus poses a prodigious health risk. Out of the many key targets, DPP-IV is one of the very imperative therapeutic targets for the treatment of diabetic patients. Objective and Methods: In our current study, we have done the in silico simulations of ADME-T properties for naturally originated potent DPP-IV inhibitors like quinovic acid, stigmasterol, quinovic acid-3-beta-D-glycopyranoside, zygophylo-side E, and lupeol. Structural topographies ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…They found that the ethanolic extracts were being able to significantly modulate the biochemical parameters like blood glucose, lipid peroxidation, and free radicals in the alloxan-induced diabetic Swiss albino mice ( Reza et al, 2019 ). Phytomolecules like kaempferol ( Ibitoye et al, 2018 ), quercetin ( Vessal et al, 2003 ), stigmasterol ( Wang et al, 2017 ; Singla and Shen, 2020 ), p-coumaric acid ( Amalan et al, 2016 ), ferulic acid ( Narasimhan et al, 2015 ), and chlorogenic acid ( Ong et al, 2013 ) may be responsible for the antidiabetic potential of Alternanthera brasiliana (L.) Kuntze.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the ethanolic extracts were being able to significantly modulate the biochemical parameters like blood glucose, lipid peroxidation, and free radicals in the alloxan-induced diabetic Swiss albino mice ( Reza et al, 2019 ). Phytomolecules like kaempferol ( Ibitoye et al, 2018 ), quercetin ( Vessal et al, 2003 ), stigmasterol ( Wang et al, 2017 ; Singla and Shen, 2020 ), p-coumaric acid ( Amalan et al, 2016 ), ferulic acid ( Narasimhan et al, 2015 ), and chlorogenic acid ( Ong et al, 2013 ) may be responsible for the antidiabetic potential of Alternanthera brasiliana (L.) Kuntze.…”
Section: Introductionmentioning
confidence: 99%
“…ex DC., including but not limited to modulation of insulin sensitivity, improvement in pancreatic insulin secretion, reduction in blood glucose level, inhibition of α-glucosidase enzyme, etc. Phytomolecules like kaempferol ( Ibitoye et al, 2018 ), quercetin ( Vessal et al, 2003 ), stigmasterol ( Wang et al, 2017 ; Singla and Shen, 2020 ), 4-hydroxybenzoic acid ( Peungvicha et al, 1998 ), β-sitosterol ( Ponnulakshmi et al, 2019 ), ellagic acid ( Fatima et al, 2015 ), ferulic acid ( Narasimhan et al, 2015 ), and chlorogenic acid ( Ong et al, 2013 ) may be responsible for the antidiabetic potential of Alternanthera sessilis (L.) R.Br. ex DC.…”
Section: Introductionmentioning
confidence: 99%
“…One significant advantage of medicinal plant-based drug development is the availability of ethnopharmacological data, which can be used to narrow down the vast number of probable leads and choose the most promising ones ( Choudhari et al, 2020 ; Singla, 2020 ). However, the integrated drug discovery approach supported by multidisciplinary fields, including medicinal chemistry, pharmacology, natural product chemistry, biochemistry, and molecular and cellular biology, is expected to lead to a better understanding of the potential of phytochemicals ( Newman and Cragg, 2016 ; Singla et al, 2020b ; Choudhari et al, 2020 ; Singla and Shen, 2020 ). A large number of phytochemicals, such as quercetin ( Rauf et al, 2018 ), fisetin ( Lall et al, 2016 ), curcumin ( Ide et al, 2018 ), genistein ( Basak et al, 2008 ), resveratrol ( Lee et al, 2014 ), have been found to modulate AR activity and expression.…”
Section: Introductionmentioning
confidence: 99%